ICAR Flexi-check Dam Rubber Dam - Jena, Susanta Kumar (Indian Farming, 2015)
The rubber check dams can be well utilized for achieving sustainable crop production and could be instrumental for enhancing crop and water productivity in watersheds. It does not have any adverse impact on environment can be easily installed, and operated by farmers of the watersheds. There is almost no maintenance except the running cost of filling (inflating) with water at the time of need.